Android-based CERMAT (Cerdas Mengenal Pubertas) Media Development in Enhancing Students Understanding of Puberty as a Part of Sex Education for Elementary School Students - Anggita, Aisya Puspa; Subali, Bambang; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2023)
This research was established because of the widespread sexual abuse of children. Additionally, students’ learning outcomes on puberty subject matter at SDN Purwoyoso 02 are yet to be considered proper. The aims of this research are developing android based CERMAT (Guide to Puberty) learning media to enhance students’ understanding about puberty on elementary school level; testing the media feasibility; and examining students’ understanding improvement on puberty through the implementation of android based CERMAT learning media. This research was using the RnD method with ADDIE development model (analyze, design, development, implementation, and evaluation). The subjects of this research are 6th grade students of SDN Purwoyoso 02 Semarang City. The data were obtained through a test with multiple choices. Through the media, material, and language expert judgements, android based CERMAT learning media was proven to be “very feasible” to be implemented. The results obtained through t-test on students’ pretest and posttest gained sig. (2-tailed) score of 0,000, which means that sig. (2-tailed) 0000 < 0,05 Ho is rejected, and Ha is accepted so, android-based CERMAT learning media can enhance students’ understanding about puberty. Meanwhile, the n-gain test of the pretest and posttest obtained a score of 0,57 (57%) and categorized “Quite Effective '' with a score difference of 25,09. Based on the result of the study, it can be inferred that android based CERMAT learning media development is considered feasible and effective in enhancing 6th grade students’ mastery of the subject matter puberty.